Application of genetic algorithms in the calculation of the optimal plan the distribution of goods - Никульченко, А. А. (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2013)
Composed method of dynamic programming and genetic algorithms suggested to find the optimal plan of distribution of the goods in multinomenclature systems with multiple distribution points and restrictions on shipments. The implementation of the proposed algorithm is completed and tested on real data.